EXPERIMENTAL STUDIES OF THE STRENGTH OF A LONG BASE FLAT WAGONS BY CARRYING OUT ENDURANCE CYCLIC FATIGUE TESTS (Transport systems and technologies, 2022)
The need for experimental validation of structural solutions concerning the frame of long-base flat wagon and assessment of the accuracy of theoretical calculations by carrying out resource cyclic fatigue tests based on the results of the recent studies analysis in the research of the strength of long-base flat wagons, was established. The methodology for carrying out resource cyclic fatigue tests of a long-base flat wagon is presented. The results of theoretical studies on determining the strength of a long-base flat wagon are described. The results of experimental studies of endurance cyclic fatigue tests of the frame of a long-wheelbase flat wagon before and after structural improvement are shown. Structural changes and improvements of the frame of the long-base flat wagon at the stage of experimental endurance cyclic fatigue tests are presented. The place of initiation and development of a crack in the structure of the frame of a long-base flat wagon is shown. Based on the results of the research, the actual strength of the elements of the wagon structure was determined and the design of the long-base flat wagon was chosen in order to prevent fatigue failure and ensure the required operational safety. The need to improve the evaluation methods of fatigue strength of welded joints of the long-wheelbase flat wagons frames at the design stage has been proven.The content of the article will contribute to the construction of new models of long-base flat wagons for mainline railway and the modernization of existing models, as well as to increase their strength and service life while in operation.
Keywords: fatigue test, endurance limit, long-base flat wagon, fatigue strength safety factor, strength, service life.